2022
DOI: 10.21532/apfjournal.v6i2.234
|View full text |Cite
|
Sign up to set email alerts
|

Integrity, Religiosity, Gender: Factors Preventing on Academic Fraud

Abstract: The purpose of this study is to explain and predict the effect of respondent integrity and religiosity in relation to the possibility of academic fraud, which is mostly done by students. The study was also supposed to look at the effect of gender on students’ academic fraud behavior. This study involved 102 accounting students from public universities in Malang, Indonesia. Researchers used survey methods to collect data, and data were analyzed by SPSS software using multiple linear regression and moderated reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The second is to investigate the variables that best explain the academic dishonesty tendency levels of the students who continue their graduate education by using the CHAID (Chi-squared Automatic Interaction Detection) analysis method. When the literature is examined (Adıbatmaz & Kurnaz, 2017;Akbaşlı et al, 2019;Akdağ & Güneş, 2002;Ayoub/Al-Salim & Aladwan, 2021;Barın et al, 2018;Bateman & Valentine, 2010;Belet-Boyacı et al, 2017;Brown, Bourke-Taylor et al, 2019;Brown, Isbel et al, 2020;Burns, et al, 1998;Chow et al, 2021;Coate & Frey, 2000;Çenberci, 2018;Çetin, 2007;Dağaşan et al, 2017;Dam, 2013;Demir & Arcagök, 2013;Duran, 2020;Eminoğlu-Küçüktepe & Küçüktepe, 2012;Eriksson & McGee, 2015;Ersoy & Özden, 2011;Gümüşgül et al, 2013;Hadjar, 2019;Hensley et al, 2013;Kadı et al, 2016;Kaymakcan, 2002;Keçeci et al, 2011;Kıral & Saracaloğlu, 2018;Kocaman-Karoğlu & Bakar-Çörez, 2020;Koç, 2018;Korn & Davidovitch, 2016;Lin & Wen, 2007;McCabe & Trevino, 1997;Nonis & Swift, 1998;Novianti, 2022;Ömür et al, 2014;Öztürk-Başpınar & Çakıroğlu, 2019;Özyurt & Eren, 2014;…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The second is to investigate the variables that best explain the academic dishonesty tendency levels of the students who continue their graduate education by using the CHAID (Chi-squared Automatic Interaction Detection) analysis method. When the literature is examined (Adıbatmaz & Kurnaz, 2017;Akbaşlı et al, 2019;Akdağ & Güneş, 2002;Ayoub/Al-Salim & Aladwan, 2021;Barın et al, 2018;Bateman & Valentine, 2010;Belet-Boyacı et al, 2017;Brown, Bourke-Taylor et al, 2019;Brown, Isbel et al, 2020;Burns, et al, 1998;Chow et al, 2021;Coate & Frey, 2000;Çenberci, 2018;Çetin, 2007;Dağaşan et al, 2017;Dam, 2013;Demir & Arcagök, 2013;Duran, 2020;Eminoğlu-Küçüktepe & Küçüktepe, 2012;Eriksson & McGee, 2015;Ersoy & Özden, 2011;Gümüşgül et al, 2013;Hadjar, 2019;Hensley et al, 2013;Kadı et al, 2016;Kaymakcan, 2002;Keçeci et al, 2011;Kıral & Saracaloğlu, 2018;Kocaman-Karoğlu & Bakar-Çörez, 2020;Koç, 2018;Korn & Davidovitch, 2016;Lin & Wen, 2007;McCabe & Trevino, 1997;Nonis & Swift, 1998;Novianti, 2022;Ömür et al, 2014;Öztürk-Başpınar & Çakıroğlu, 2019;Özyurt & Eren, 2014;…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…On the other hand, when students' frequency of cheating according to gender was examined in the literature, it was observed that females come to the fore in terms of rarely cheating and that males come to the fore in terms of cheating more frequently (Duran, 2020). In addition, there are studies not reporting significant differences between males and females in terms of their cheating tendencies (Ayoub/Al-Salim & Aladwan, 2021;Barın et al, 2018;Çenberci, 2018;Çetin, 2007;Dam, 2013;Keçeci et al, 2011;Lin & Wen, 2007;Novianti, 2022;Pearson, 2019;Szabo & Underwood, 2004;Tümkaya, 2019;Ünlü & Eroğlu, 2012).…”
mentioning
confidence: 99%
“…Cheating behavior by students is influenced by perceptions of behavioral control, subjective norms, and attitudes, which are also related to cheating intentions among students (Yusliza et al, 2022). According to Novianti (2022), academic cheating is one of the impacts of a lack of self-integrity and a low level of religiosity.…”
Section: Introductionmentioning
confidence: 99%